Pengaruh Fertilitas Terhadap Partisipasi Tenaga Kerja Perempuan - Harsoyo, Andri; Sulistyaningrum, Eny (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No. 2, Agustus 2018 (pp. 147-253)DO - 10.24843/JEKT.2018.v11.i02.p01, 2018)
Indonesia, like other countries in the world, is experiencing a downward trend in the total fertility rate and an increasing trend in the female labor force participation rate. This study looks at the effect of female fertility on job supply in Indonesia by using IFLS data and the instrumental variable (IV) estimation technique first introduced by Angrist and Evans (1996; 1998) conducted in the United States. This study shows how parental preferences are related to different sexes of children as identification of fertility towards women's participation in the labor market. The results of this study indicate that fertility with the approach of the number of children owned and then instrumented by looking at the sex of the child resulted in a decrease in the supply of female labor. The magnitude of the effect on the working age group is that there is a decrease in work participation of around 52-54 percent and a decrease in overall work hours of around 23 hours / week.